Investigating determinants of intentions and behaviours of farmers towards a circular economy for water recycling in paddy field. Issue 4 (3rd April 2023) - Moradnezhadi, Homayoon; Aliabadi, Vahid; Gholamrezai, Saeed; Mahdizade, Hossein
ABSTRACT: To implement a circular economy for water recycling and its optimal use, it is imperative to understand the behaviours of farmers and the farming systems they belong to because psychological effects usually influence and sometimes weaken technical solutions. The present study addresses farmers' behaviours in rice-fish farming systems towards a circular economy with an emphasis on water recycling. Using the theory of planned behaviour and structural equation modelling of partial least squares (PLS-SEM), the factors determining the intentions and behaviours of 500 farmers in these systems toward the circular economy were evaluated. The results show that attitudes (β = 0.271), subjective norms (β = 0.174), and perceived behavioural control (β = 0.215) positively influence farmers' intention in the rice-fish farming systems for the better implementation of water recycling methods. Additionally, farmers' intentions (β = 0.145), attitudes (β = 0.115), perceived behavioural control (β = 0.291), pressures (β = 0.109), barriers (β = −0.286), and enablers (β = 0.117) affect the behaviour of these systems toward the circular economy positively. In this regard, perceived behaviour control and barriers have the strongest positive and negative effects on the circular economy, respectively. Our study shows that most rice-fish farming systems have a positive intention, but they have failed in implementing the best practices of circular economy development with an emphasis on water recycling due to some important barriers. The research proposes some measures to reduce the gap between intention and behaviour and the accomplishment of the circular economy in the context of water.